Solid waste: its implication for health and risk of vector borne diseases - Mohd Tohit, Nor Faiza; Hassan, Noor Artika; Rusli, Mohammad Farhan; Mohammad Aidid, Edre; Mohd Rus, Razman (Zibeline International Publishing, 2019)
Solid waste management is a growing challenge to many countries. The implications of poorly managed waste on health are numerous. Improper waste management serve as the breeding places for many vectors resulting in proliferation of vector-borne diseases. This article highlights the impact of improper solid waste management on the public health and the increase risk of vector-borne diseases.